INFLUENCE OF MATERNAL FEEDING PRACTICE ON STUNTING AMONG CHILDREN AGED 6 TO 59 MONTHS FROM PENDEM VILLAGE, BATU CITY, INDONESIA - Amaliya, Sholihatul; Hayati, Yati Sri; Azizah, Nurona (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2023)
Introduction: Stunting is a condition of chronic malnutrition due to inadequate nutritional intake and is still a major health problem in Indonesia. Reducing the stunting rate can be done by reducing one of the risk factors of stunting, namely inadequate nutrition, which is influenced by the feeding practice in children under five years. This study aims to examine the relationship between complementary feeding practices on the incidence of stunting in Pendem Village, Batu City.Method: A case-control study was conducted and involved 30 children under five with stunting in the village of Pendem Batu City as a case group and 30 children with non-stunting conditions as a control. The instrument used in this study was a complementary feeding practice questionnaire. Furthermore, the data will be analyzed using an independent t-test and Mann-Whitney test.Result: The practice of giving complementary food has a significant relationship with the incidence of stunting in the village of Pendem, Batu City (p=0.015; <0,05), especially in the sub-category of complementary feeding safety (p=0.014) and the responsive complementary feeding (p=0.007). In the sub-category, the accuracy of complementary foods (p=0.176) and the adequacy of complementary foods (p=0.83) were not significantly related to the incidence of stunting in the village of Pendem Koa Batu.Conclusions: The practice of giving MPASI has a significant relationship with the incidence of stunting, especially in the sub-category of safety and responsive giving of MPASI.